Writing Teaching Strategies by Junior High School English Teacher - Johannes Fikki Fernando Damanik; Riris Debora Hutasoit; Lampita Deniska Sitorus; Erikson Saragih (Jurnal Ilmiah Wahana Pendidikan, 2022)
One of the things that teachers are concerned with in order to fulfill their teaching goals in their classrooms is teaching strategies. Teachers must be innovative and expand their knowledge of instructional methods and procedures, such as teaching writing strategies. This research is disscuss about the strategies used by teacher in teaching writing strategies in classroom. To collect the data, the researchers make questionnaire distributed by google form. The findings of the study revealed that English teachers' strategies were group discussion, mind mapping, look in up dictionary. However, the teacher's reaction to the strategy was good, as their opinion was that the strategy they applied was satisfying and helpful in helping students improve their writing ability.